How to Assess and Prevent Risk of Diabetic Foot Ulcer - Kharisma Pratama; Wuriani Wuriani; Cau Kim Jiu; Syahid Amrullah; Jaka Pradika; Yenni Lukita; Usman Usman; Hartono Hartono; Indri Erwhani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The discovery of problems related to health status was the beginning of the idea to carry out activities with the basic theme "Semiloka on Assessment of Complications of Diabetes Mellitus in Pontianak, Kalimantan Barat Pontianak City. The program aimed to increase knowledge and skills of participants in assesing and preventing the risk of diabetic foot ulcer (DFU). The program consist of providing education about early detection and prevention of DFU, then followed by the practice of detecting and carrying out nursing actions to prevent the occurrence of DFU by participants. Most of the participants were aged 56-65 years 15 (50%), female sex 19 (63%), last education was high school 15 (50%), housewife work 13 (43.33%), the majority had DM < 10 years 23 (76.67%), and normal sensation 23 (76.67%). Participants took part in the activity from start to finish, and participants were able to apply a risk assessment for the occurrence of DFU.